The Role of the Regional Disaster Management Agency (BPBD) in Preventing Flood Disasters in Mandailing Natal Regency - Hasanuddin; Junita, Audia; Siregar, Nina Siti Salmaniah (Universitas Medan Area, 2025)
Higher than usual rainfall and an inability to absorb water optimally have caused flooding in Mandailing Natal Regency. Geographical conditions that include mountains, highlands, lowlands, and coasts also contribute to the potential for complex disasters. This study aims to analyze the role of the Regional Disaster Management Agency (BPBD) in flood prevention and identify inhibiting factors. A qualitative descriptive approach was used, with data obtained through interviews, observations, and documentation. The results of the study indicate that BPBD carries out its role through pre-disaster mitigation, including media appeals, training, construction of safety structures, non-structural mitigation based on community empowerment, and the establishment of Disaster Resilient Villages. At the emergency response stage, BPBD deploys a Rapid Reaction Team (TRC) to assess the situation, while post-disaster recovery is carried out through infrastructure reconstruction, victim trauma assistance, establishment of command posts, damage inventory, and evaluation. The main obstacles include budget limitations and cross-sector coordination. The conclusion of this study confirms that optimizing the role of BPBD requires better synergy with the central government and the community to increase the effectiveness of flood prevention and handling in Mandailing Natal.